2021
DOI: 10.1016/j.wombi.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological exploration of parenting after birth trauma: Mothers perceptions of the first year

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In addition to preterm birth, other difficult birth experiences and related trauma ( McDonald et al, 2011 , Molloy et al, 2020 ), as well as difficult infant temperament ( Mills-Koonce et al, 2007 , Oddi et al, 2013 ), can negatively influence a mother’s mental health and parenting. Exploration of the impact of these factors on the maternal brain remains very limited.…”
Section: How Stress Exposure Is Associated With Brain Adjustment To Mmentioning
confidence: 99%
“…In addition to preterm birth, other difficult birth experiences and related trauma ( McDonald et al, 2011 , Molloy et al, 2020 ), as well as difficult infant temperament ( Mills-Koonce et al, 2007 , Oddi et al, 2013 ), can negatively influence a mother’s mental health and parenting. Exploration of the impact of these factors on the maternal brain remains very limited.…”
Section: How Stress Exposure Is Associated With Brain Adjustment To Mmentioning
confidence: 99%
“…Research on parental stress and burnout has suggested that parents who experience burnout are more likely to engage in child maltreatment, placing children at risk for detrimental short-and long-term outcomes (Griffith, 2020). Additionally, women who experience birth trauma have described disconnection with their infants, lack of confidence in their parental decision making, distressing memory gaps of the immediate post-partum period, and physical recovery that overwhelmed their capabilities to parent the way they had imagined they would (Molloy et al, 2020). Chronic fatigue has been shown to increase parental irritability and angry and fatigued parents are less likely to be able to attend and engage in play (Giallo et al, 2013).…”
Section: Mental Health Strain Of Mothers With Young Childrenmentioning
confidence: 99%
“…The experience of difficult childbirth labour appeared to be re-occurring with flashbacks triggering emotional distress. Similarly, Molloy et al 8 recently explored the perceptions of parenting after birth trauma. They reported that mothers who suffered birth trauma are at higher risk of anxiety and fear of their child’s health and their parenting capability.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health conditions impact significantly on maternal functioning and prevent the mother from being emotionally available to meet the demands of her child. 7 , 8 Poor maternal mental health (MMH) could have lifelong consequences on the children. It predicts stunted growth and adverse neurological development in the children of the affected mothers and disturbances in the mother and child bonding and healthy childhood attachment with long-term adverse effects.…”
Section: Introductionmentioning
confidence: 99%